Plant Stanol Esters Affect Serum Cholesterol Concentrations of Hypercholesterolemic Men and Women in a Dose-dependent Manner - Hallikainen, Maarit A.; Sarkkinen, Essi S.; Uusitupa, Matti I.J. (The Journal of nutrition, 2000)
The effect of plant stanol ester on serum cholesterol is dose-dependent. However, it is not clear what the dose is beyond which no additional benefit can be obtained. Therefore, we determined the dose-response relationship for serum cholesterol with different doses of plant stanol ester in hypercholesterolemic subjects. In a single-blind design each of 22 men or women consumed five different doses of plant stanol [target (actual) intake 0 (0), 0.8 (0.8), 1.6 (1.6), 2.4 (2.3), 3.2 (3.0) g/d] added as plant stanol esters to margarine for 4 wk. The order of dose periods was randomly determined. Serum total cholesterol concentration decreased (calculated in reference to control) by 2.8% (P = 0.384), 6.8% (P < 0.001), 10.3% (P < 0.001) and 11.3% (P < 0.001) by doses from 0.8 to 3.2 g. The respective decreases for LDL cholesterol were 1.7% (P = 0.892), 5.6% (P < 0.05), 9.7% (P < 0.001) and 10.4% (P < 0.001). Although the decreases were numerically greater with 2.4 and 3.2 g doses than with the 1.6 g dose, these differences were not significant (P = 0.054–0.516). Serum plant stanols rose slightly, but significantly with the dose (P < 0.001). Apolipoprotein B concentration was decreased significantly already at the dose of 0.8 g (8.7%, P < 0.001). Apolipoprotein E genotype did not affect the lipid responses. We conclude that significant reduction of serum total and LDL cholesterol concentrations is reached with the 1.6-g stanol dose, and increasing the dose from 2.4 to 3.2 g does not provide clinically important additional effect.